(untitled) (Eurasian Research Bulletin, 2022)
The modern pace of life, whether we like it or not, sets its own time frame, keeps us in the eternal "rhythm of dance", the non-observance of which knocks us out of the rut. Today, an overwhelming number of people are engaged in learning a foreign language. Each of them has his own goal of learning, some are eternal business trips, others are traveling. Every day people are increasingly eager to learn a foreign language in a short period of time and first of all go for help in various language learning organizations. But we decided to simplify the task and get acquainted with the most effective ways to learn a foreign language. Learning a foreign language (especially new words and expressions) is hard and painstaking work that requires constant cramming and spending a lot of time. Is this true? Is it really impossible to avoid these unpleasant moments for us? The article is devoted to the consideration of various, in our opinion, effective, ways of learning English. The publication considers the possibility of using author’s methods that contribute to the rapid learning of foreign languages, and in particular English